COMBINATION THERAPY AS INITIAL TREATMENT FOR HYPERTENSION: A SYSTEMATIC REVIEW - Persson Jeffry, Erick (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Hypertension is a modifiable risk factor for cardiovascular disease, the leading cause of mortality in the world, and cardiovascular disease is a risk that may be minimized by managing hypertension. Even within the normal range, even a little elevation in blood pressure is associated with an increased risk. More than 70% of persons being treated for primary hypertension will eventually require the use of at least two antihypertensive drugs. Seventy percent or more of persons treated for primary hypertension will require at least two antihypertensive drugs, either initially as combination therapy or as add-on therapy if monotherapy and lifestyle modifications do not offer adequate blood pressure control. Combination therapy for the treatment of hypertension employs four key medication classes: thiazide diuretics, calcium channel blockers, angiotensin-converting enzyme inhibitors (ACEIs), and angiotensin receptor blockers (ARBs). Since 2003, individuals with hypertension have been prescribed two medications. Several people require dual antihypertensive medication treatment, which has been shown to be helpful, particularly for those with blood pressure >160/90 mmHg.